Developing strategic capacity in Olympic sport organisations - Robinson, L.; Minikin, B. (Sport, Business and Management, 2011)
The purpose of this paper is to set out research that aimed to understand how the internal capabilities of Olympic sport organisations can be addressed. Design/methodology/approach - The research was carried out by a mixed-method, multi phase approach, using senior sport administrators in the Pacific region. Findings - The research developed a tool for analysing the "readiness" of sport organisations to deliver programmes and services. Research limitations/implications - This research has developed a framework for the internal diagnosis of organisations. Practical implications - Managers can use the tool to inform their strategic planning. Originality/value - The paper presents a new and unique tool for assessing organisational capacity.